Evaluation of the Genotoxicity of Endodontic Materials for Deciduous Teeth Using the Comet Assay - Nilton Cesar Nogueira dos Santos; Bruno Marques Soares; Cláudia do Ó Pessoa; Livia Maria Andrade de Freitas; João Pedro Pedrosa Cruz; Maria Emília Santos Pereira Ramos; Matheus Melo Pithon; Eneida Moraes de Marcílio Cerqueira (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate genotoxicity of zinc oxide, P. A. calcium hydroxide, mineral trioxide aggregate and an iodoform paste using comet assay on human lymphocytes. Material and Methods: Two positive controls were used: methyl-methanesulfonate for the P.A. calcium hydroxide and mineral trioxide aggregate; and doxorubicin for the iodoform paste and zinc oxide. There were also two negative controls: distilled water for the P.A. calcium hydroxide and mineral trioxide aggregate; and DMSO for the iodoform paste and zinc oxide. Comets were identified using fluorescence microscopy and 100 of them were counted on each of the three slides analyzed per drug test. A damage index was established, taking into consideration the score pattern that had previously been determined from the size and intensity of the comet tail. Analysis of variance, followed by Tukey's test, was used to compare the means of the DNA damage indices. Results: The DNA damage index observed for mineral trioxide aggregate (7.08 to 8.58) and P.A. calcium hydroxide (6.50 to 8.33), which were similar to negative control index. On the other hand, damage index for zinc oxide (104.7 to 218.50) and iodoform paste (115.7 to 210.7) were similar to positive control index. Conclusion: Iodoform paste and zinc oxide showed genotoxicity at all concentrations used.